Optimizing Capacity to Meet Production Planning and Implementing Blue Economy Practices at the Popcorn Factory in Surabaya - Damastutik, Nandaryani; Handayani, Wiwik (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Production planning is the process of organizing and controlling the flow of materials in and out of the production system to meet consumer needs with the right quantity and timing while keeping production costs low. Based on the analysis, the popcorn factory in Surabaya has not maximized capacity management, as evidenced by the occurrence of surplus and deficit in available capacity (CA) during certain periods. The Surabaya popcorn factory does not fully utilize capacity management because the company produces either more or fewer products than the demand. Overproduction can lead to warehouse overstocking, while underproduction prevents the company from meeting consumer needs. The purpose of this research is to analyze and evaluate the capacity of resources and production equipment using forecasting techniques with minimum MSE (Mean Squared Error) to obtain an optimal production capacity plan and make appropriate capacity planning recommendations to ensure all consumer demands are met.